Australia as a Powerbroker on Refugee Protection in Southeast Asia: The Relationship with Indonesia - Kneebone, Susan (Refuge: Canada’s Journal on Refugees, 2017)
Using the example of Australian-Indonesian cooperation on deterrence of asylum seekers in transit through Indonesia to Australia, this article challenges the view that Australia is a regional hegemon. It does this through two main methods. First, it engages in a close analysis of the shifting relationship between the two countries on refugee and asylum-seeker issues through different periods since 2001 to 2016. This demonstrates that the relationship is in fact more nuanced than previously suggested by other scholars. Second, it refers to Thomas Pedersen’s political concept of “cooperative hegemony,” which focuses upon “ideationalinstitutional realism” as a lens through which to view regional co-operation. It analyzes the institutional nature of the Australian–Indonesian cooperation relationship in the Southeast Asian context, to demonstrate that Australia has not established itself as a model of “cooperative hegemony.”